Science and “narrativity”. Towards a classification of the uses of narrative in the exact and natural sciences - Koval, Martín Ignacio (2022)
This article addresses some manifestations of narrative in science with the broader intention of contributing to the understanding of its use in factual domains. First, taking as a starting point some previous approaches to the problem of “narrativity”, a theoretical-analytical model is proposed that specifies ten conditions of narrativity. Then, the aim is to determine the areas of scientific discursive production that are more permeable to narrative textuality based on a measurement of the degrees of narrativity of different textual genres. Thus, the differences between texts that report on established knowledge and those that provide new knowledge are explored; a distinction is made between the institutional communication of science and its dissemination; the persuasive and illustrative uses of narrative are addressed; and the field of historical sciences is delimited as a privileged realm of narrative explanation. Finally, the article proposes some conclusions aimed at showing the usefulness of applying the approach of the degrees of narrativity to think about the reception of the discourse of science and what has been called the “narrative effect”.